PP-33 Codeine and tramadol use in a paediatric population in new zealand. Issue 10 (20th September 2017) - Reith,; Simpson,; Medlicott,; Smith,
Abstract : Background: There are concerns regarding codeine in the <2 years age group, particularly in the context of post-tonsillectomy analgesia. Tramadol, although ap-proved for children in New Zealand (NZ), is not approved. <2 years age. From 2014, practice guidelines in NZ dis-couraged the use of codeine and tramadol in children. The WHO analgesic ladder for children advocates a two-step approach: simple analgesia (paracetamol or ibupro-fen) as the first step with the second step for moderate or severe pain being morphine. The aim of the present study was to examine the dispensing of codeine, tramadol and morphine for children in NZ in order to identify trends in usage. Methods: All NZ community dispensing data for codeine phosphate, tramadol and morphine were extracted from national administrative databases (National Pharmaceu-tical Collection and National Minimum Dataset) for the period 01 January 2010 to 31 December 2015. The data were summarised for each calendar year by age group:<2 years, 2 to <6 years, 6 to <12 years and 12 to <17 years. Results: In the <2 year age group there was little use of either codeine or tramadol, but usage of both increased to 2014, with an abrupt drop in usage of codeine in 2015. In the 2 to <6 year age group there was greater use of codeine, also increasing to 2014 with an abrupt drop in usage in 2015; tramadol usage increased in both 2014 and 2015. In the older age group there was greater usage of both codeine and tramadol with progressively increas-ing use of tramadol. Morphine use in all the age groups appeared stable. Conclusion: These data suggest that prescribers have adopted recommendations with regard to codeine but there may be substitution of codeine with tramadol.